The Effect Of Fe Tablet Consumption On Hemoglobin (Hb) Increase In Pregnant Women: A Systematic Literature Review - Cahya Skania, Pratiwi; Dasuki, Djaswadi; Utami, Fitriana Siswi (Universitas Muhammadiyah Sidoarjo, 2020)
Anemia is still a problem in developing countries. The World Health Organization states that there are still more than 50 percent of women in the world suffering from anemia. anemia can cause life-threatening bleeding, miscarriage, low birth weight and premature birth. WHO defines anemia as a condition where the hemoglobin level is less than 11 mg / dL in the first and last trimester or 10.5 mg / dL in the second trimester or the hematocrit level is less than 37 percent. The study aim to determine the effect of Fe tablets consumption on hemoglobin (Hb) level increase in pregnant women and to find out the factors related to the compliance of pregnant women taking Fe tablets. This Systematic Literature Publication and Science uses databases with the period 2008-2018. The selection of articles was based on the inclusion and exclusion criteria. The Appraisal study employed The Joanna Briggs Institute Critical Appraisal Tools. Taking Fe tablets is very influential in increasing levels of Hb in pregnant women who suffer from anemia. Effective iron supplements to reduce anemia in pregnancy. Support from family and closest people has an important role in increasing adherence to taking Fe tablets.